Digital nomads' willingness to stay – A combined analysis of SEM and fsQCA results - Andrade, T. A.; Dias, Á.; Patuleia, M.; Pereira, L. (Journal of Tourism and Services, 2023)
Lisbon is a multicultural city with a business center that hosts major technology companies and professionals in the field, including digital nomads. High demand for tourist accommodation and the arrival of foreigners to work in the country have led to an imbalance between the supply and affordable cost of real estate for residents of the capital. This work aims to survey and determine whether digital nomads in Lisbon intend to settle in the city or are just passing through. To identify the combination of factors that influence digital nomads’ decision-making, we conducted a quantitative study using survey data tested through structural equation modelling and configurational analysis by fsQCA. The results show that while the decision to stay in the city is heavily influenced by community attachment, we found three configurations that reveal distinct patterns of digital nomads’ intention to stay in the city. These results suggest that policymakers need to consider that digital nomads are not a homogeneous group. This study makes an important contribution to the understanding of behavioral intentions and is, to the authors’ knowledge, the first to identify different configurations based on digital nomads’ intentions to stay in a city.